The Administration of Curriculum using English as a Medium of instruction in Accordance with European Union of Primary Schools in Bangkok under The office the private Education Commission - Duangchurn, Patcharaporn; Untaweesin, Apinun; Triwijitkhasem, Woranuch (Arts of Management Journal, 2021)
This research aimed to analyze the problem and propose a guideline for the administration of curriculum using English as a medium of instruction in accordance with European union of primary schools in Bangkok under the office of the private education commission. The research was based on a Delphi technique designated by 15 specialists. The research instruments and statistics were open-ended questions and question of the estimated scales in which the selected expert answered the questions three times. The statistics used were the median and the interquartile range. The research results found the following problems were: 1) there was no clear policy in the preparation of the curriculum; 2) teachers do not have knowledge of teaching and learning according to the CEFR framework; 3) the curriculum did not provide a CEFR-based measurement and evaluation; 4) the curriculum does not have a clear goal setting using the six CEFR proficiency levels; and 5) There was no development of the curriculum to meet international standards, guidelines were: 1) establish a clear policy for preparing the curriculum; 2)empower teachers to gain knowledge and understanding of the curriculum; 3) develop the curriculum in relation to the CEFR framework; 4) design communication English learning activities in the curriculum; and 5) schedule a student’s language proficiency test based on the CEFR level of language proficiency and assess it for ongoing course development.